Capillary electrophoresis methods development and sensitivity enhancement strategies for the separation of industrial and environmental chemicals - McLaughlin, G.M.; Weston, A.; Hauffe, K.D. (Journal of Chromatography A, 1996)
This paper focuses on capillary electrophoresis (CE) methods development and sensitivity enhancement strategies for the separation of charged and neutral species of interest to industrial and environmental laboratories. Areas addressed include: (a) free solution and micellar electrokinetic capillary chromatography (MECC) methods development strategies; (b) the use of coated capillaries with MECC and reversed polarity to improve separation speed; (c) size separation using a sieving polymer; (d) the use of specific and selective detection techniques to detect environmentally important analytes and metabolites; (e) automated sample concentration techniques to enhance sensitivity by >1000×. Numerous analyte classes are used to illustrate solutions for industrial and environmental problems. These classes include chlorinated phenols, phenoxy acid herbicides, aromatic acids, isomerized α- and β-hop acids, nitroaromatic and nitramine compounds, acidic dyes, linear benzene alkyl sulfonates (LAS), inorganic anions, and charged polymers. Procedures to improve resolution and selectivity are discussed along with methods to enhance sensitivity of detection. Finally, unified methods development strategies to separate and detect analytes in the industrial and environmental setting are described.